Pengaruh Brand Image dan Brand Personality terhadap Brand Loyalty pada Coffee Shop - Ismail Gafar Sidik; Ernawan Dwi Hanartyo (GEMILANG: Jurnal Manajemen dan Akuntansi, 2026)
As competition becomes increasingly fierce, brand identity and character become key to building customer loyalty. This study aims to analyze the influence of brand personality and brand image on brand loyalty among coffee shop consumers. The research method used is a quantitative approach with the Structural Equation Modeling (SEM) analysis technique. Data were collected through an online questionnaire using a purposive sampling technique to 130 respondents who had bought coffee in the Jakarta and Tangerang areas. The results showed that brand personality and brand image had a significant effect on brand loyalty. This indicates that a strong brand character and a positive brand image can increase customer loyalty to a coffee shop. This study has limitations, including geographically limited samples and online data collection methods that may not represent the entire consumer population. Therefore, it is recommended that further research expand the sampling area and consider other factors such as price and promotion. This study contributes to business actors in designing marketing strategies based on brand personality and brand image to increase customer loyalty.